A promoter toolbox for tissue-specific expression supporting translational research in cassava (Manihot esculenta) - Zierer, Wolfgang; Anjanappa, Ravi Bodampalli; Lamm, Christian; Chang, Shu-Heng; Gruissem, Wilhelm; Sonnewald, Uwe (Frontiers in Plant Science, 2022)
There is an urgent need to stimulate agricultural output in many tropical and subtropical countries of the world to combat hunger and malnutrition. The starchy crop cassava (Manihot esculenta), growing even under sub-optimal conditions, is a key staple food in these regions, providing millions of people with food. Cassava biotechnology is an important technique benefiting agricultural progress, but successful implementation of many biotechnological concepts depends on the availability of the right spatiotemporal expression tools. Yet, well-characterized cassava promoters are scarce in the public domain. In this study, we investigate the promoter activity and tissue specificity of 24 different promoter elements in stably transformed cassava plants. We show that many of the investigated promoters, especially from other species, have surprisingly low activity and/or tissue specificity, but feature several promoter sequences that can drive tissue-specific expression in either autotrophic-, transport- or storage tissues. We especially highlight pAtCAB1, pMePsbR, and pSlRBCS2 as strong and specific source promoters, pAtSUC2, pMeSWEET1-like, and pMeSUS1 as valuable tools for phloem and phloem parenchyma expression, and pStB33, pMeGPT, pStGBSS1, as well as pStPatatin Class I, as strong and specific promoters for heterotrophic storage tissues. We hope that the provided information and sequences prove valuable to the cassava community by contributing to the successful implementation of biotechnological concepts aimed at the improvement of cassava nutritional value and productivity.
CRIS-Team WoS Importer:2023-01-20

Auxin signaling and vascular cambium formation enable storage metabolism in cassava tuberous roots - Rüscher, David; Corral, José María; Carluccio, Anna Vittoria; Klemens, Patrick A. W.; Gisel, Andreas; Stavolone, Livia; Neuhaus, H. Ekkehard; Ludewig, Frank; Sonnewald, Uwe; Zierer, Wolfgang (Journal of Experimental Botany, 2021)
Cassava storage roots are among the most important root crops worldwide, and represent one of the most consumed staple foods in sub-Saharan Africa. The vegetatively propagated tropical shrub can form many starchy tuberous roots from its stem. These storage roots are formed through the activation of secondary root growth processes. However, the underlying genetic regulation of storage root development is largely unknown. Here we report distinct structural and transcriptional changes occurring during the early phases of storage root development. A pronounced increase in auxin-related transcripts and the transcriptional activation of secondary growth factors, as well as a decrease in gibberellin-related transcripts were observed during the early stages of secondary root growth. This was accompanied by increased cell wall biosynthesis, most notably increased during the initial xylem expansion within the root vasculature. Starch storage metabolism was activated only after the formation of the vascular cambium. The formation of non-lignified xylem parenchyma cells and the activation of starch storage metabolism coincided with increased expression of the KNOX/BEL genes KNAT1, PENNYWISE, and POUND-FOOLISH, indicating their importance for proper xylem parenchyma function.
CRIS-Team WoS Importer:2021-07-02

Carbon usage in yellow-fleshed Manihot esculenta storage roots shifts from starch biosynthesis to cell wall and raffinose biosynthesis via the myo-inositol pathway - Gutschker, Sindy; Rüscher, David; Rabbi, Ismail Y.; Rosado-Souza, Laise; Pommerrenig, Benjamin; Pauly, Markus; Robertz, Stefan; van Doorn, Anna M.; Schlereth, Armin; Neuhaus, H. Ekkehard; Fernie, Alisdair R.; Reinert, Stephan; et al. (Plant Journal, 2024)
Cassava is a crucial staple crop for smallholder farmers in tropical Asia and Sub-Saharan Africa. Although high yield remains the top priority for farmers, the significance of nutritional values has increased in cassava breeding programs. A notable negative correlation between provitamin A and starch accumulation poses a significant challenge for breeding efforts. The negative correlation between starch and carotenoid levels in conventional and genetically modified cassava plants implies the absence of a direct genomic connection between the two traits. The competition among various carbon pathways seems to account for this relationship. In this study, we conducted a thorough analysis of 49 African cassava genotypes with varying levels of starch and provitamin A. Our goal was to identify factors contributing to differential starch accumulation. Considering carotenoid levels as a confounding factor in starch production, we found that yellow- and white-fleshed storage roots did not differ significantly in most measured components of starch or de novo fatty acid biosynthesis. However, genes and metabolites associated with myo-inositol synthesis and cell wall polymer production were substantially enriched in high provitamin A genotypes. These results indicate that yellow-fleshed cultivars, in comparison to their white-fleshed counterparts, direct more carbon toward the synthesis of raffinose and cell wall components. This finding is underlined by a significant rise in cell wall components measured within the 20 most contrasting genotypes for carotenoid levels. Our findings enhance the comprehension of the biosynthesis of starch and carotenoids in the storage roots of cassava.
CRIS-Team Scopus Importer:2024-07-12
Keywords: carotenoid content; cassava; cell wall components; Manihot esculenta; myo-inositol; provitamin A; raffinose; starch content

Cassava Metabolomics and Starch Quality - Rosado-Souza, Laise; David, Laure C.; Drapal, Margit; Fraser, Paul D.; Hofmann, Jörg; Klemens, Patrick A.W.; Ludewig, Frank; Neuhaus, H. Ekkehard; Obata, Toshihiro; Perez-Fons, Laura; Schlereth, Armin; Sonnewald, Uwe; et al. (Current Protocols in Plant Biology, 2019)
Cassava plays an important role as a staple food for more than 800 million people in the world due to its ability to maintain relatively high productivity even in nutrient-depleted soils. Even though cassava has been the focus of several breeding programs and has become a strong focus of research in the last few years, relatively little is currently known about its metabolism and metabolic composition in different tissues. In this article, the absolute content of sugars, organic acids, amino acids, phosphorylated intermediates, minerals, starch, carotenoids, chlorophylls, tocopherols, and total protein as well as starch quality is described based on multiple analytical techniques, with protocols specifically adjusted for material from different cassava tissues. Moreover, quantification of secondary metabolites relative to internal standards is presented using both non-targeted and targeted metabolomics approaches. The protocols have also been adjusted to apply to freeze-dried material in order to allow processing of field harvest samples that typically will require long-distance transport. © 2019 The Authors. Basic Protocol 1: Metabolic profiling by gas chromatography-mass spectrometry (GC-MS) Support Protocol 1: Preparation of freeze-dried cassava material Support Protocol 2: Preparation of standard compound mixtures for absolute quantification of metabolites by GC-MS Support Protocol 3: Preparation of retention-time standard mixture Basic Protocol 2: Determination of organic acids and phosphorylated intermediates by ion chromatography-mass spectrometry (IC-MS) Support Protocol 4: Preparation of standards and recovery experimental procedure Basic Protocol 3: Determination of soluble sugars, starch, and free amino acids Alternate Protocol: Determination of soluble sugars and starch Basic Protocol 4: Determination of anions Basic Protocol 5: Determination of elements Basic Protocol 6: Determination of total protein Basic Protocol 7: Determination of non-targeted and targeted secondary metabolites Basic Protocol 8: Determination of carotenoids, chlorophylls, and tocopherol Basic Protocol 9: Determination of starch quality.
CRIS-Team Scopus Importer:2019-12-24
Keywords: chemotypes; Manihot esculenta; metabolite classification; metabolite profiling; metabolomics

Cold-Triggered Induction of ROS- and Raffinose Metabolism in Freezing-Sensitive Taproot Tissue of Sugar Beet - Keller, Isabel; Müdsam, Christina; Rodrigues, C. Martins; Kischka, Dominik; Zierer, Wolfgang; Sonnewald, Uwe; Harms, Karsten; Czarnecki, Olaf; Fiedler-Wiechers, Karin; Koch, Wolfgang; Neuhaus, H. Ekkehard; Ludewig, Frank; et al. (Frontiers in Plant Science, 2021)
Sugar beet (Beta vulgaris subsp. vulgaris) is the exclusive source of sugar in the form of sucrose in temperate climate zones. Sugar beet is grown there as an annual crop from spring to autumn because of the damaging effect of freezing temperatures to taproot tissue. A collection of hybrid and non-hybrid sugar beet cultivars was tested for winter survival rates and freezing tolerance. Three genotypes with either low or high winter survival rates were selected for detailed study of their response to frost. These genotypes differed in the severity of frost injury in a defined inner region in the upper part of the taproot, the so-called pith. We aimed to elucidate genotype- and tissue-dependent molecular processes during freezing and combined analyses of sugar beet anatomy and physiology with transcriptomic and metabolite profiles of leaf and taproot tissues at low temperatures. Freezing temperatures induced strong downregulation of photosynthesis in leaves, generation of reactive oxygen species (ROS), and ROS-related gene expression in taproots. Simultaneously, expression of genes involved in raffinose metabolism, as well as concentrations of raffinose and its intermediates, increased markedly in both leaf and taproot tissue at low temperatures. The accumulation of raffinose in the pith tissue correlated with freezing tolerance of the three genotypes. We discuss a protective role for raffinose and its precursors against freezing damage of sugar beet taproot tissue.
CRIS-Team Scopus Importer:2021-10-01
Keywords: freezing; pith; raffinose; reactive oxygen species; sugar beet

Corrigendum: A promoter toolbox for tissue-specific expression supporting translational research in cassava (Manihot esculenta)(Front. Plant Sci., (2022), 13, (1042379), 10.3389/fpls.2022.1042379) - Zierer, Wolfgang; Anjanappa, Ravi Bodampalli; Lamm, Christian; Chang, Shu Heng; Gruissem, Wilhelm; Sonnewald, Uwe (Frontiers in Plant Science, 2024)
In the published article, there was an error in the legend for Figure 2 and the legend for Figure S2 as published. In the Figure 2 legend, subfigure F2 – F6 were falsely labeled subfigure H2 – H6. In the Figure S2 legend, the subfigures C-F were incorrectly labeled and the labeling for subfigures G-H was missing. The corrected legend appears below. FIGURE 2 Representative GUS staining pattern of at least three events from pAtCAB1, pStLS1, pAtRBCS3B, pMeGBSS1, pStSSS3, and pStSTP1 promoter-reporter plants. pAtCAB1::GUS = A1) Source leaf (Inlay = Close-up), B1) Sink leaf, C1) Emerging leaves, D1) Petiole cross-section, E1) Upper stem cross-section, F1) Lower stem cross-section, G1) Storage root cross-section, H1) Fibrous roots, I1) GUS expression levels of four pAtCAB1::GUS lines relative to three pCaMV35S::GUS lines in %. pStLS1::GUS = A2) Source leaf, B2) Sink leaf, C2) Petiole cross-section, D2) Upper stem cross-section, E2) Storage root cross-section, F2) Fibrous roots. pAtRBCS3B::GUS = A3) Source leaf, B3) Sink leaf, C3) Petiole cross-section, D3) Upper stem cross-section, E3) Storage root cross-section, F3) Fibrous roots. pMeGBSS1::GUS = A4) Source leaf, B4) Sink leaf, C4) Petiole cross-section, D4) Upper stem cross-section, E4) Storage root cross-section, F4) Fibrous roots. pStSSS3::GUS = A5) Source leaf, B5) Sink leaf, C5) Petiole cross-section, D5) Upper stem cross-section, E5) Storage root cross-section, F5) Fibrous roots. pStSTP1::GUS = A6) Source leaf, B6) Sink leaf, C6) Petiole cross-section, D6) Upper stem cross-section, E6) Storage root cross-section, F6) Fibrous roots. Plants were either grown on the field at NCHU experimental station Taichung, Taiwan or in a greenhouse in Erlangen, Germany. Tissues from approximately 3-month-old cassava plants were used. FIGURE S2 Representative GUS staining pattern of three pCaMV35S::GUS promoter-reporter lines. A) Source leaf, B) Sink leaf, C) Emerging leaves, D) Petiole cross-section, E) Upper stem cross-section, F) Lower stem cross-section, G) Storage root cross-section, H) Fibrous roots. The authors apologize for these errors and state that this does not change the scientific conclusions of the article in any way. The original article has been updated.
CRIS-Team Scopus Importer:2024-05-24
Keywords: biotechnology; cassava; parenchyma; phloem; promoter; storage root; tissue; xylem

Efficient sugar utilization and transition from oxidative to substrate-level phosphorylation in high starch storage roots of African cassava genotypes - Lamm, Christian; Rabbi, Ismail Y.; Medeiros, David Barbosa; Rosado-Souza, Laise; Pommerrenig, Benjamin; Dahmani, Ismail; Rüscher, David; Hofmann, Jörg; van Doorn, Anna M.; Schlereth, Armin; Neuhaus, H. Ekkehard; Fernie, Alisdair R.; et al. (Plant Journal, 2023)
Cassava's storage roots represent one of the most important sources of nutritional carbohydrates worldwide. Particularly, smallholder farmers in sub-Saharan Africa depend on this crop plant, where resilient and yield-improved varieties are of vital importance to support steadily increasing populations. Aided by a growing understanding of the plant's metabolism and physiology, targeted improvement concepts already led to visible gains in recent years. To expand our knowledge and to contribute to these successes, we investigated storage roots of eight cassava genotypes with differential dry matter content from three successive field trials for their proteomic and metabolic profiles. At large, the metabolic focus in storage roots transitioned from cellular growth processes toward carbohydrate and nitrogen storage with increasing dry matter content. This is reflected in higher abundance of proteins related to nucleotide synthesis, protein turnover, and vacuolar energization in low starch genotypes, while proteins involved in sugar conversion and glycolysis were more prevalent in high dry matter genotypes. This shift in metabolic orientation was underlined by a clear transition from oxidative- to substrate-level phosphorylation in high dry matter genotypes. Our analyses highlight metabolic patterns that are consistently and quantitatively associated with high dry matter accumulation in cassava storage roots, providing fundamental understanding of cassava's metabolism as well as a data resource for targeted genetic improvement.
CRIS-Team Scopus Importer:2023-07-21
Keywords: energy metabolism; glycolysis; Manihot esculenta; metabolomics; oxidative phosphorylation; proteomics; source/sink; starch metabolism; sugar metabolism; TCA-cycle

Metabolic profiles of six African cultivars of cassava (Manihot esculenta Crantz) highlight bottlenecks of root yield - Obata, Toshihiro; Klemens, Patrick A.W.; Rosado-Souza, Laise; Schlereth, Armin; Gisel, Andreas; Stavolone, Livia; Zierer, Wolfgang; Morales, Nicolas; Mueller, Lukas A.; Zeeman, Samuel C.; Ludewig, Frank; Stitt, Mark; et al. (Plant Journal, 2020)
Cassava is an important staple crop in sub-Saharan Africa, due to its high productivity even on nutrient poor soils. The metabolic characteristics underlying this high productivity are poorly understood including the mode of photosynthesis, reasons for the high rate of photosynthesis, the extent of source/sink limitation, the impact of environment, and the extent of variation between cultivars. Six commercial African cassava cultivars were grown in a greenhouse in Erlangen, Germany, and in the field in Ibadan, Nigeria. Source leaves, sink leaves, stems and storage roots were harvested during storage root bulking and analyzed for sugars, organic acids, amino acids, phosphorylated intermediates, minerals, starch, protein, activities of enzymes in central metabolism and yield traits. High ratios of RuBisCO:phosphoenolpyruvate carboxylase activity support a C3 mode of photosynthesis. The high rate of photosynthesis is likely to be attributed to high activities of enzymes in the Calvin–Benson cycle and pathways for sucrose and starch synthesis. Nevertheless, source limitation is indicated because root yield traits correlated with metabolic traits in leaves rather than in the stem or storage roots. This situation was especially so in greenhouse-grown plants, where irradiance will have been low. In the field, plants produced more storage roots. This was associated with higher AGPase activity and lower sucrose in the roots, indicating that feedforward loops enhanced sink capacity in the high light and low nitrogen environment in the field. Overall, these results indicated that carbon assimilation rate, the K battery, root starch synthesis, trehalose, and chlorogenic acid accumulation are potential target traits for genetic improvement.
CRIS-Team Scopus Importer:2020-03-17
Keywords: carbon fixation; cassava; chlorogenic acid; enzyme activity; K battery; nitrogen metabolism; photosynthesis; root yield; source/sink limitation; starch synthesis

Multi-omics data integration reveals link between epigenetic modifications and gene expression in sugar beet (Beta vulgaris subsp. vulgaris) in response to cold - Gutschker, Sindy; Corral, José María; Schmiedl, Alfred; Ludewig, Frank; Koch, Wolfgang; Fiedler-Wiechers, Karin; Czarnecki, Olaf; Harms, Karsten; Keller, Isabel; Martins Rodrigues, Cristina; Pommerrenig, Benjamin; Neuhaus, H. Ekkehard; et al. (BMC Genomics, 2022)
BACKGROUND: DNA methylation is thought to influence the expression of genes, especially in response to changing environmental conditions and developmental changes. Sugar beet (Beta vulgaris ssp. vulgaris), and other biennial or perennial plants are inevitably exposed to fluctuating temperatures throughout their lifecycle and might even require such stimulus to acquire floral competence. Therefore, plants such as beets, need to fine-tune their epigenetic makeup to ensure phenotypic plasticity towards changing environmental conditions while at the same time steering essential developmental processes. Different crop species may show opposing reactions towards the same abiotic stress, or, vice versa, identical species may respond differently depending on the specific kind of stress. RESULTS: In this study, we investigated common effects of cold treatment on genome-wide DNA methylation and gene expression of two Beta vulgaris accessions via multi-omics data analysis. Cold exposure resulted in a pronounced reduction of DNA methylation levels, which particularly affected methylation in CHH context (and to a lesser extent CHG) and was accompanied by transcriptional downregulation of the chromomethyltransferase CMT2 and strong upregulation of several genes mediating active DNA demethylation. CONCLUSION: Integration of methylomic and transcriptomic data revealed that, rather than methylation having directly influenced expression, epigenetic modifications correlated with changes in expression of known players involved in DNA (de)methylation. In particular, cold triggered upregulation of genes putatively contributing to DNA demethylation via the ROS1 pathway. Our observations suggest that these transcriptional responses precede the cold-induced global DNA-hypomethylation in non-CpG, preparing beets for additional transcriptional alterations necessary for adapting to upcoming environmental changes.
CRIS-Team Scopus Importer:2022-02-25
Keywords: Abiotic stress; Beta vulgaris subsp. vulgaris; Cold response; DNA methylation; Epigenetics; Omics; RNA-seq; WGBS

Phloem-specific expression of Yang cycle genes and identification of novel Yang cycle enzymes in Plantago and Arabidopsis. - Pommerrenig, Benjamin; Feussner, Kirstin; Zierer, Wolfgang; Rabinovych, Valentyna; Klebl, Franz; Feussner, Ivo; Sauer, Norbert (The Plant Cell, 2011)
The 5-methylthioadenosine (MTA) or Yang cycle is a set of reactions that recycle MTA to Met. In plants, MTA is a byproduct of polyamine, ethylene, and nicotianamine biosynthesis. Vascular transcriptome analyses revealed phloem-specific expression of the Yang cycle gene 5-METHYLTHIORIBOSE KINASE1 (MTK1) in Plantago major and Arabidopsis thaliana. As Arabidopsis has only a single MTK gene, we hypothesized that the expression of other Yang cycle genes might also be vascular specific. Reporter gene studies and quantitative analyses of mRNA levels for all Yang cycle genes confirmed this hypothesis for Arabidopsis and Plantago. This includes the Yang cycle genes 5-METHYLTHIORIBOSE-1-PHOSPHATE ISOMERASE1 and DEHYDRATASE-ENOLASE-PHOSPHATASE-COMPLEX1. We show that these two enzymes are sufficient for the conversion of methylthioribose-1-phosphate to 1,2-dihydroxy-3-keto-5-methylthiopentene. In bacteria, fungi, and animals, the same conversion is catalyzed in three to four separate enzymatic steps. Furthermore, comparative analyses of vascular and nonvascular metabolites identified Met, S-adenosyl Met, and MTA preferentially or almost exclusively in the vascular tissue. Our data represent a comprehensive characterization of the Yang cycle in higher plants and demonstrate that the Yang cycle works primarily in the vasculature. Finally, expression analyses of polyamine biosynthetic genes suggest that the Yang cycle in leaves recycles MTA derived primarily from polyamine biosynthesis.

Phloem-Specific Methionine Recycling Fuels Polyamine Biosynthesis in a Sulfur-Dependent Manner and Promotes Flower and Seed Development. - Zierer, Wolfgang; Hajirezaei, Mohammad R.; Eggert, Kai; Sauer, Norbert; von Wirén, Nicolaus; Pommerrenig, Benjamin (Plant Physiology, 2016)
The Yang or Met Cycle is a series of reactions catalyzing the recycling of the sulfur (S) compound 5'-methylthioadenosine (MTA) to Met. MTA is produced as a by-product in ethylene, nicotianamine, and polyamine biosynthesis. Whether the Met Cycle preferentially fuels one of these pathways in a S-dependent manner remained unclear so far. We analyzed Arabidopsis (Arabidopsis thaliana) mutants with defects in the Met Cycle enzymes 5-METHYLTHIORIBOSE-1-PHOSPHATE-ISOMERASE1 (MTI1) and DEHYDRATASE-ENOLASE-PHOSPHATASE-COMPLEX1 (DEP1) under different S conditions and assayed the contribution of the Met Cycle to the regeneration of S for these pathways. Neither mti1 nor dep1 mutants could recycle MTA but showed S-dependent reproductive failure, which was accompanied by reduced levels of the polyamines putrescine, spermidine, and spermine in mutant inflorescences. Complementation experiments with external application of these three polyamines showed that only the triamine spermine could specifically rescue the S-dependent reproductive defects of the mutant plants. Furthermore, expressing gene-reporter fusions in Arabidopsis showed that MTI1 and DEP1 were mainly expressed in the vasculature of all plant parts. Phloem-specific reconstitution of Met Cycle activity in mti1 and dep1 mutant plants was sufficient to rescue their S-dependent mutant phenotypes. We conclude from these analyses that phloem-specific S recycling during periods of S starvation is essential for the biosynthesis of polyamines required for flowering and seed development.

STP10 encodes a high-affinity monosaccharide transporter and is induced under low-glucose conditions in pollen tubes of Arabidopsis. - Rottmann, Theresa; Zierer, Wolfgang; Subert, Christa; Sauer, Norbert; Stadler, Ruth (Journal of Experimental Botany, 2016)
Pollen tubes are fast growing, photosynthetically inactive cells. Their energy demand is covered by specific transport proteins in the plasma membrane that mediate the uptake of sugars. Here we report on the functional characterization of AtSTP10, a previously uncharacterized member of the SUGAR TRANSPORT PROTEIN family. Heterologous expression of STP10 cDNA in yeast revealed that the encoded protein catalyses the high-affinity uptake of glucose, galactose and mannose. The transporter is sensitive to uncouplers of transmembrane proton gradients, indicating that the protein acts as a hexose-H(+)symporter. Analyses of STP10 mRNA and STP10 promoter-reporter gene studies revealed a sink-specific expression pattern of STP10 in primordia of lateral roots and in pollen tubes. This restriction to sink organs is mediated by intragenic regions of STP10 qPCR analyses with cDNA of in vitro grown pollen tubes showed that STP10 expression was down-regulated in the presence of 50mM glucose. However, in pollen tubes of glucose-insensitive plants, which lack the glucose sensor hexokinase1 (HXK1), no glucose-induced down-regulation of STP10 expression was detected. A stp10T-DNA insertion line developed normally, which may point towards functional redundancy. The data presented in this paper indicate that a high-affinity glucose uptake system is induced in growing pollen tubes under low glucose conditions and that this regulation may occur through the hexokinase pathway.

Symplasmic phloem loading and subcellular transport in storage roots are key factors for carbon allocation in cassava - Rüscher, David; Vasina, Viktoriya V.; Knoblauch, Jan; Bellin, Leo; Pommerrenig, Benjamin; Alseekh, Saleh; Fernie, Alisdair R.; Neuhaus, H. Ekkehard; Knoblauch, Michael; Sonnewald, Uwe; Zierer, Wolfgang (Plant Physiology, 2024)
Cassava (Manihot esculenta) is a deciduous woody perennial shrub that stores large amounts of carbon and water in its storage roots. Previous studies have shown that assimilating unloading into storage roots happens symplasmically once secondary anatomy is established. However, mechanisms controlling phloem loading and overall carbon partitioning to different cassava tissues remain unclear. Here, we used a combination of histological, transcriptional, and biochemical analyses on different cassava tissues and at different timepoints to better understand source–sink carbon allocation. We found that cassava likely utilizes a predominantly passive symplasmic phloem loading strategy, indicated by the lack of expression of genes coding for key players of sucrose transport, the existence of branched plasmodesmata in the companion cell/bundle sheath interface of minor leaf veins, and very high leaf sucrose concentrations. Furthermore, we showed that tissue-specific changes in anatomy and non-structural carbohydrate contents are associated with tissue-specific modification in gene expression for sucrose cleavage/synthesis, as well as subcellular compartmentalization of sugars. Overall, our data suggest that carbon allocation during storage root filling is mostly facilitated symplasmically and is likely mostly regulated by local tissue demand and subcellular compartmentalization.
CRIS-Team Scopus Importer:2024-10-11

Symplasmic phloem unloading and radial post-phloem transport via vascular rays in tuberous roots of Manihot esculenta - Mehdi, Rabih; Lamm, Christian; Bodampalli Anjanappa, Ravi; Müdsam, Christina; Saeed, Muhammad; Klima, Janine; Kraner, Max; Ludewig, Frank; Knoblauch, Michael; Gruissem, Wilhelm; Sonnewald, Uwe; Zierer, Wolfgang (Journal of Experimental Botany, 2019)
Cassava (Manihot esculenta) is one of the most important staple food crops worldwide. Its starchy tuberous roots supply over 800 million people with carbohydrates. Yet, surprisingly little is known about the processes involved in filling of those vital storage organs. A better understanding of cassava carbohydrate allocation and starch storage is key to improving storage root yield. Here, we studied cassava morphology and phloem sap flow from source to sink using transgenic pAtSUC2::GFP plants, the phloem tracers esculin and 5(6)-carboxyfluorescein diacetate, as well as several staining techniques. We show that cassava performs apoplasmic phloem loading in source leaves and symplasmic unloading into phloem parenchyma cells of tuberous roots. We demonstrate that vascular rays play an important role in radial transport from the phloem to xylem parenchyma cells in tuberous roots. Furthermore, enzymatic and proteomic measurements of storage root tissues confirmed high abundance and activity of enzymes involved in the sucrose synthase-mediated pathway and indicated that starch is stored most efficiently in the outer xylem layers of tuberous roots. Our findings form the basis for biotechnological approaches aimed at improved phloem loading and enhanced carbohydrate allocation and storage in order to increase tuberous root yield of cassava.
CRIS-Team Scopus Importer:2019-11-05
Keywords: Apoplast; cassava; CFDA; esculin; morphology; phloem; ray; starch; SUC2; symplast

The Cassava Source–Sink project: opportunities and challenges for crop improvement by metabolic engineering - Sonnewald, Uwe; Fernie, Alisdair R.; Gruissem, Wilhelm; Schlaepfer, Pascal; Anjanappa, Ravi B.; Chang, Shu-Heng; Ludewig, Frank; Rascher, Uwe; Muller, Onno; Van Doorn, Anna M.; Rabbi, Ismail Y.; Zierer, Wolfgang (Plant Journal, 2020)
Cassava (Manihot esculenta Crantz) is one of the important staple foods in Sub-Saharan Africa. It produces starchy storage roots that provide food and income for several hundred million people, mainly in tropical agriculture zones. Increasing cassava storage root and starch yield is one of the major breeding targets with respect to securing the future food supply for the growing population of Sub-Saharan Africa. The Cassava Source–Sink (CASS) project aims to increase cassava storage root and starch yield by strategically integrating approaches from different disciplines. We present our perspective and progress on cassava as an applied research organism and provide insight into the CASS strategy, which can serve as a blueprint for the improvement of other root and tuber crops. Extensive profiling of different field-grown cassava genotypes generates information for leaf, phloem, and root metabolic and physiological processes that are relevant for biotechnological improvements. A multi-national pipeline for genetic engineering of cassava plants covers all steps from gene discovery, cloning, transformation, molecular and biochemical characterization, confined field trials, and phenotyping of the seasonal dynamics of shoot traits under field conditions. Together, the CASS project generates comprehensive data to facilitate conventional breeding strategies for high-yielding cassava genotypes. It also builds the foundation for genome-scale metabolic modelling aiming to predict targets and bottlenecks in metabolic pathways. This information is used to engineer cassava genotypes with improved source–sink relations and increased yield potential.
CRIS-Team Scopus Importer:2020-07-10
Keywords: biotechnology; Cassava; Manihot esculenta; sink; source; yield

Tuber and Tuberous Root Development - Zierer, Wolfgang; Rüscher, David; Sonnewald, Uwe; Sonnewald, Sophia (Annual Review of Plant Biology, 2021)
Root and tuber crops have been an important part of human nutrition since the early days of humanity, providing us with essential carbohydrates, proteins, and vitamins. Today, they are especially important in tropical and subtropical regions of the world, where they help to feed an ever-growing population. Early induction and storage organ size are important agricultural traits, as they determine yield over time. During potato tuberization, environmental and metabolic status are sensed, ensuring proper timing of tuberization mediated by phloem-mobile signals. Coordinated cellular restructuring and expansion growth, as well as controlled storage metabolism in the tuber, are executed. This review summarizes our current understanding of potato tuber development and highlights similarities and differences to important tuberous root crop species like sweetpotato and cassava. Finally, we point out knowledge gaps that need to be filled before a complete picture of storage organ development can emerge.
CRIS-Team Scopus Importer:2021-07-02
Keywords: cassava; development; potato; storage root; sweetpotato; tuber

Vernalization alters sink and source identities and reverses phloem translocation from taproots to shoots in sugar beet - Rodrigues, Cristina Martins; Müdsam, Christina; Keller, Isabel; Zierer, Wolfgang; Czarnecki, Olaf; Corral, José María; Reinhardt, Frank; Nieberl, Petra; Fiedler-Wiechers, Karin; Sommer, Frederik; Schroda, Michael; Mühlhaus, Timo; et al. (The Plant Cell, 2020)
During their first year of growth, overwintering biennial plants transport Suc through the phloem from photosynthetic source tissues to storage tissues. In their second year, they mobilize carbon from these storage tissues to fuel new growth and reproduction. However, both the mechanisms driving this shift and the link to reproductive growth remain unclear. During vegetative growth, biennial sugar beet (Beta vulgaris) maintains a steep Suc concentration gradient between the shoot (source) and the taproot (sink). To shift from vegetative to generative growth, they require a chilling phase known as vernalization. We studied sugar beet sink-source dynamics upon vernalization and showed that before flowering, the taproot underwent a reversal from a sink to a source of carbohydrates. This transition was induced by transcriptomic and functional reprogramming of sugar beet tissue, resulting in a reversal of flux direction in the phloem. In this transition, the vacuolar Suc importers and exporters TONOPLAST SUGAR TRANSPORTER2;1 and SUCROSE TRANSPORTER4 were oppositely regulated, leading to the mobilization of sugars from taproot storage vacuoles. Concomitant changes in the expression of floral regulator genes suggest that these processes are a prerequisite for bolting. Our data will help both to dissect the metabolic and developmental triggers for bolting and to identify potential targets for genome editing and breeding.
CRIS-Team Scopus Importer:2020-10-23